THE STORY OF GODDESS DRUPADI AS INSPIRATION FOR ILLUSTRATED STORYBOOK CREATION - Dhiyaurrahman, M. Audi (Eduarts: Jurnal Pendidikan Seni, 2026)
Illustration is a form visual communication that powerfully coveys narratives through imagery. This prototype was inspired by the figure of Dewi Drupadi from the epic Mahabharata, serving as the central theme for a picture storybook. Drupadi was chosen due to her multifaceted character, embodying values such as courage, resilience, and sincerity amidst trials. These values are reinterpreted through visual storytelling in a modern illustrative style, designed to appeal to readers ranging from teenagers to young adults. The creative process involved several stages: literature review, story development, character design, and page layout composition review. The artwork was produced digitally using Procreate, with narrative illustration style that blends elements of fantasy and cultural tradition. Character expressions and atmospheric settings are rendered in detail to enhance the reader’s imaginative and emotional engagement. This prototype serves not only as a medium for developing illustration skills but also as a cultural effort to preserve and reintroduce classic tales through fresh visual interpretations. The resulting illustrated storybook aims to be both educational and inspirational, offering a contemporary gateway for younger generations to rediscover the richness of Mahabharata legends through art.